2018
DOI: 10.3389/fphar.2018.00939
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Synthesis: From Nature to the Chemical Modification and Synthesis and Their Applications as Drugs and Nutrients

Abstract: Bile acids (BAs) are amphiphilic molecules with 24 carbon atoms and consist of a hydrophobic and a rigid steroid nucleus, to which are attached a hydrophilic hydroxyl group and a flexible acidic aliphatic side chain. The steroidal core of BAs constitutes a saturated cyclopentanoperhydrophenanthrene skeleton, consisting of three six-membered (A, B, and C) and one five-membered ring (D). Primary BAs are produced in the hepatocytes, while secondary BAs are formed by modifying the primary BAs in the intestinal lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 47 publications
(104 reference statements)
0
100
0
13
Order By: Relevance
“…We have also confirmed the changes in the fecal contents of bile acids. Bile acids are derivatives of steroids and are ubiquitously contained in the bile of vertebrates [42]. After being endogenously synthesized from cytochrome P450-mediated cholesterol metabolism in the liver and excreted into the duodenum, bile acids are mixed with phospholipids such as phosphatidylcholine and cholesterols to form micelles.…”
Section: Discussionmentioning
confidence: 99%
“…We have also confirmed the changes in the fecal contents of bile acids. Bile acids are derivatives of steroids and are ubiquitously contained in the bile of vertebrates [42]. After being endogenously synthesized from cytochrome P450-mediated cholesterol metabolism in the liver and excreted into the duodenum, bile acids are mixed with phospholipids such as phosphatidylcholine and cholesterols to form micelles.…”
Section: Discussionmentioning
confidence: 99%
“…In einem vielstufigen, von Enzymen der Zytochrom-P450-Familie katalysierten Prozess wird das Sterangerüst des Cholesterins hydroxyliert, hydriert und die Seitenkette am D-Ring oxidativ zu einem Fettsäurerest verkürzt (▶ Abb. 1, [5]). Das geschwindigkeitsbestimmende Schlüsselenzym der Gallensäurebildung ist die mikrosomale Cholesterin-7α-Hydroxylase (CYP7A1).…”
Section: Gallensäurendie Klassische Sichtunclassified
“…Mit der Identifizierung der Gallensäuren als Liganden des FXR ergaben sich neue medikamentöse Behandlungen mit modifizierten Gallensäuren. Ein Beispiel dafür ist die Obeticholsäure (Ocaliva ® ), ein CDCA-Derivat, zur Behandlung der primären biliären Cholangitis [5].…”
Section: Gallensäuren Als Signalmoleküleunclassified
See 1 more Smart Citation
“…The primary bile acids are synthesized from cholesterol with a complex series of reactions involving 17 different enzymes found in endoplasmic reticulum, mitochondria, cytoplasm and peroxisomes [17]. Recent studies have identified four major biosynthetic pathways of bile acids, named the Classic / Neutral pathway, the Alternative / Acidic pathway, the Yamasaki pathway and the 25-hydroxylation pathway [18,19] (Figure 1). Cholesterol is a C27-sterol and has a double bond at position C5 (cholest-5-en-3β-ol).…”
Section: Pathways Of Bile Acid Synthesismentioning
confidence: 99%